2023
DOI: 10.1108/jiabr-10-2022-0267
|View full text |Cite
|
Sign up to set email alerts
|

Does Islamic financial development foster economic growth? International evidence

Abstract: Purpose Several studies link Islamic finance to economic growth. There are at least two major limitations in these investigations. First, the proxy used to measure Islamic finance may not represent the whole impact of Islamic finance on economic growth because it only considers a subset of variables like Islamic banks’ deposits or sukuk issuance, etc. Second, it is difficult to extrapolate findings to other markets because most studies were conducted in just one nation or a small group of countries. Overcoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Islamic finance has been extensively studied about economic growth, with findings showing its positive impact on sustainable development. Studies show that Islamic finance contributes significantly to economic growth [13]- [16]. By promoting risk sharing and emphasizing real economic activities, Islamic finance encourages productive investments in sectors that benefit society [17].…”
Section: Economic Growth and Islamic Financementioning
confidence: 99%
See 1 more Smart Citation
“…Islamic finance has been extensively studied about economic growth, with findings showing its positive impact on sustainable development. Studies show that Islamic finance contributes significantly to economic growth [13]- [16]. By promoting risk sharing and emphasizing real economic activities, Islamic finance encourages productive investments in sectors that benefit society [17].…”
Section: Economic Growth and Islamic Financementioning
confidence: 99%
“…Islamic finance in Indonesia has shown significant potential in driving economic growth by mobilizing resources for productive investments, increasing financial inclusion, and promoting ethical financial practices [6], [13], [18]. Studies show that Islamic finance, particularly through Islamic banking, contributes to reducing income inequality in Indonesia, in line with the goal of inclusive growth [19].…”
Section: Role Of Islamic Finance In Promoting Economic Growthmentioning
confidence: 99%
“…Understanding interest rates' fluctuations in the Pakistani environment is crucial, as several studies have demonstrated how crucial they are in influencing depositor behavior and bank profitability. The study conducted by Butt, Sadaqat, and Shear (2023) investigated the effects of variations in interest rates on the profitability of banks in Pakistan. The study showed that interest rate variations had a major impact on banks' net interest margins and overall profitability, emphasizing how crucial interest rate risk management is for financial institutions doing business in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These changes have had a variety of effects on the commercial banking system. Second, several other non-financial institutions provided deposit facilities to clients (Butt, Sadaqat, and Shear, 2023). Monetary policy has plays an important part in developing economy.…”
Section: Introductionmentioning
confidence: 99%